2023
DOI: 10.2174/1871520622666220321091022
|View full text |Cite
|
Sign up to set email alerts
|

A Focused Review on Molecular Signalling Mechanisms of Ginsenosides Anti-Lung Cancer and Anti-inflammatory Activities

Abstract: Background: Ginseng (Panax ginseng Meyer) is a cultivated medicinal herb that has been widely available in the Asian region since the last century. Ginseng root is used worldwide in Oriental medicine. Currently, the global mortality and infection rates for lung cancer and inflammation are significantly increasing. Therefore, various preventive methods related to the activity of ginsenosides have been used for lung cancer as well as inflammation. Methods: Web-based searches were performed on Web of Science, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…In this study, based on UPLC–MS/MS analysis, we successfully identified and selected 20 prototype components for further pharmacokinetic studies. These prototype components have shown therapeutic potential in inhibiting cancer cells [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, based on UPLC–MS/MS analysis, we successfully identified and selected 20 prototype components for further pharmacokinetic studies. These prototype components have shown therapeutic potential in inhibiting cancer cells [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…23 Ginsenosides have been shown to exert anti-lung cancer activity by modulating multiple pathways of growth and metastasis. 24 However, there is no detailed review addressing the protective role of ginsenosides in lung protection. In this review, the molecular mechanisms of ginsenosides against lung cancer in terms of proliferation, apoptosis, autophagy, metastasis, drug resistance and immunological effects will be discussed in detail, along with the nano-delivery systems and their protective effects and molecular mechanisms against pulmonary inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Since prehistoric times, plant-based medications have served as the foundation of traditional medical practices used in many nations, including Egypt, India, and China [31]. Due to their unique effectiveness, safety, and economical impact on cancer, natural products today play an important role in cancer prevention and therapy [32,33]. With approximately 300 species dispersed over all of the major tropical zones, Cissus is the biggest genus in the Vitaceae family of grapes [34].…”
Section: Introductionmentioning
confidence: 99%